Biểu hiện nhiễu điện hóa của thép không gỉ SS 304 ăn mòn lỗ trong dung dịch chứa FeCl3 - Chiến, Nguyễn Văn; Cường, Lê Văn; Tĩnh, Nguyễn Trọng; Long, Phạm Đức (Vietnam Journal of Chemistry, 2015)
The use of electrochemical noise (EN) technique for the investigation and monitoring of corrosion has allowed many interesting advances in the corrosion science in recent years. The correlation analysis of spectral current electrochemical noise and potential electrical noise data recording over time obtained from the electrodeplate304 stainless steel corrosion pitting in FeCl3 solution in a state of stable natural ventilation were studied. The experimental investigation by conventional electrochemical methods and surface morphology was used to compare the coordination type of corrosion holes for 304 stainless steel in the corrosive environment conditions. The obtained transients in potential and current time correlate with the surface morphology analysis. The analysis results show that the transition observed in real time series corresponding to the activity of developing germ pits on the surface of the electrodes.